Essay Writing Performances at the Tertiary Level:The Case of Indonesian EFL Learners - Achmad Kholili; Feri Ferdiyanto (Universitas Hamzanwadi, 2020)
Some methods and approaches have been put into practice by stakeholders, including both teachers and lecturers in the teaching and learning process of English, specifically writing. Nevertheless, writing English is still burdensome for some learners, particularly EFL learners. For this reason, the survey study was conducted to point out the mistakes made by the students in composing an essay. Eleven EFL learners, coming from non-Anglicized linguistic and cultural backgrounds at the Institut Ilmu Keislaman Zainul Hasan Genggong, Probolinggo, East Java, Indonesia were taken out as the sample of this study. The major instruments distributed were writing prompts and a semi-structured interview. Their writing results were scored with the scoring scale adopted from Jacobs (1981), cited in (Weigle, 2002, p. 116). From the five components in writing, consisting of Vocabulary, Content, Language Use related to the ideas in the text, Organization of the text, and Mechanics, the results demonstrate that Language use (Tense, Preposition, Run-ons, and Articles)and Mechanics (Spelling, Punctuation, and Capitalization) are dominant errors committed by the EFL Learners in writing.